2010
DOI: 10.1007/s10571-010-9531-y
|View full text |Cite
|
Sign up to set email alerts
|

Kainate-Mediated Excitotoxicity Induces Neuronal Death in the Rat Spinal Cord In Vitro via a PARP-1 Dependent Cell Death Pathway (Parthanatos)

Abstract: Kainate is an effective excitotoxic agent to lesion spinal cord networks, thus providing an interesting model for investigating basic mechanisms of spinal cord injury. The present study aimed at revealing the type and timecourse of cell death in rat neonatal spinal cord preparations in vitro exposed to 1 h excitotoxic insult with kainate. Substantial numbers of neurons rather than glia showed pyknosis (albeit without necrosis and with minimal apoptosis occurrence) already apparent on kainate washout and peakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 84 publications
2
67
0
Order By: Relevance
“…A similar process has also been suggested to occur in the spinal cord after an acute lesion (Scott et al 1999;Genovese et al 2005;Kuzhandaivel et al 2010). Our in vitro model using the rat-isolated spinal cord subjected to a transient excitotoxic stimulus by the glutamate receptor agonist kainate has demonstrated substantial neuronal losses attributable to parthanatos (with preservation of glia) that was attenuated by the PARP-1 inhibitor 6(5H)-phenanthridinone (PHE; Kuzhandaivel et al 2010). Nonetheless, this observation needs validation with electrophysiological recording to prove whether locomotor network activity in vitro is preserved as well.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…A similar process has also been suggested to occur in the spinal cord after an acute lesion (Scott et al 1999;Genovese et al 2005;Kuzhandaivel et al 2010). Our in vitro model using the rat-isolated spinal cord subjected to a transient excitotoxic stimulus by the glutamate receptor agonist kainate has demonstrated substantial neuronal losses attributable to parthanatos (with preservation of glia) that was attenuated by the PARP-1 inhibitor 6(5H)-phenanthridinone (PHE; Kuzhandaivel et al 2010). Nonetheless, this observation needs validation with electrophysiological recording to prove whether locomotor network activity in vitro is preserved as well.…”
Section: Introductionmentioning
confidence: 66%
“…During the process of neuronal excitotoxicity, hyperactivation of the intracellular enzyme poly(ADP-ribose)polymerase-1 (PARP-1) is thought to be a major step to trigger a non-apoptotic form of cell death termed parthanatos (Narasimhan et al 2003;Wang et al 2009;Kuzhandaivel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We previously used a less selective antagonist of PARP-1, namely PHE, and observed analogous results on the rat isolated spinal cord (Kuzhandaivel et al 2010b). Since PJ 34 is reported to be also an inhibitor of metalloproteinases (Nicolescu et al 2009), we cannot exclude the possibility that this effect contributed to the current data.…”
Section: Neuroprotection By Pj 34mentioning
confidence: 69%
“…Our previous data demonstrated that, in the rat isolated spinal cord, neurons showed PAR-immunopositivity and pyknotic nuclei 24 h after a large concentration (1 mM) of kainate (Kuzhandaivel et al 2010b). Thus, we first investigated whether kainate induced strong expression of PAR also in organotypic slices and what timecourse this phenomenon might follow.…”
Section: Time and Concentration Dependence Of Kainate Excitotoxicity mentioning
confidence: 93%
See 1 more Smart Citation